2011
DOI: 10.1146/annurev-genom-090810-183119
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Speech and Language Disorders

Abstract: Vocal communication mediated by speech and language is a uniquely human trait, and has served an important evolutionary role in the development of our species. Deficits in speech and language functions can be of numerous types, including aphasia, stuttering, articulation disorders, verbal dyspraxia, and specific language impairment; language deficits are also related to dyslexia. Most communication disorders are prominent in children, where they are common. A number of these disorders have been shown to cluste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 110 publications
(114 reference statements)
1
49
0
4
Order By: Relevance
“…This strategy has facilitated the identification of genes or chromosomal loci implicated in other learning disorders, such as developmental verbal dyspraxia. 33,34 Executive function or WM deficits have been reported in genetic neurodevelopmental disorders associated with ID and physical abnormalities, like Down's syndrome or Williams syndrome. 35,36 Various approaches, including linkage analysis and association studies, have indicated various candidate genes, such as ROBO1 or CHD13, associated with low WM performances as a specific endophenotype of a cognitive dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…This strategy has facilitated the identification of genes or chromosomal loci implicated in other learning disorders, such as developmental verbal dyspraxia. 33,34 Executive function or WM deficits have been reported in genetic neurodevelopmental disorders associated with ID and physical abnormalities, like Down's syndrome or Williams syndrome. 35,36 Various approaches, including linkage analysis and association studies, have indicated various candidate genes, such as ROBO1 or CHD13, associated with low WM performances as a specific endophenotype of a cognitive dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in addition to the situation where one phenotype corresponds to many genotypes, we can also expect that one genotype corresponds to multiple phenotypes. Table 2 outlines the range of experimental paradigms that have been applied to molecular studies of developmental communication disorders to tackle their heterogeneous genetic architecture and make best use of available resources (Newbury and Monaco 2010;Kang and Drayna 2011;Deriziotis and Fisher 2013;Newbury et al 2014). This research field is at a relatively early stage of development and studies need (when possible) to take an unbiased genomewide approach to gene-hunting.…”
Section: Paradigms In the Genetic Investigation Of Developmental Commmentioning
confidence: 99%
“…Although speech and language are not easily distinguished, they are different from each other [1]. Speech is defined as the mechanical aspect of vocalization for communication, and includes articulation, voice and fluency.…”
Section: Introductionmentioning
confidence: 99%